Trabajo de grado: Importacion de repuestos para bicicletas (Marca shimano, kit de arrastre y juego de cambios) (2022)
This project has as purpose determine feasibility of importing Shimano brand bicycle spare parts from China, the spare parts mainly comprise two: Gearbox and Drag Kit. The study was developed through surveys of establishments and end customers in the fifth zone of the town of Usme in Bogotá, in order to find the non-conformities, expectations and requirements focused on the chosen products that are marketed in this area. Later an analysis and study was carried out of the main competitors, importers and distributors of spare parts for bicycles to national level where we focus on the trajectory of the market and prices.